Environmental education at school: unsuitable actions from human being to the environment and its consequences - Rossi , Mayara; Oliveira , Vanusa Maria de; Mello, Geison Jader; Leão, Marcelo Franco (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
This experience report seeks to report the application of an SD whose objective was to make students understand the problems caused to the environment due to human action. The participants were 27 students of the 4th year of Elementary School of a State Public School, in Juína-MT. The SD was applied and developed during the month of November in 2021, totaling 14 hours divided into 7 meetings with 2-hours. Students were evaluated throughout the process, believing that learning assessment should always occur and not just through tests and evaluations. Among the main results, it can be highlighted that the students were able to understand the definition of each action worked on in the classroom (excessive use of pesticides, burning, deforestation, consumerism, and waste of water), as well as their consequences for the environment and living beings. Thus, it was possible to sensitize children to conscious actions based on a sense of responsibility and the common good. Finally, regarding the participation and execution of activities, a significant number of students were excited, active, and enthusiastic with good arguments for the discussions held in the classroom, reaching more than 50% of correct answers in the kahoot quiz with questions related to the theme.
Keywords: Anthropic Actions; Environmental education; Environment